KESULITAN GURU MENDEFENISIKAN DAN MENERAPKAN KONSEP MERDEKA BELAJAR - Herly Janet Lesilolo (TANGKOLEH PUTAI, 2022)
Independent learning which has been rolled out since 2019 until this research was conducted has not shown a change in the attitude of teachers' teaching and independent student learning. The teacher's limited understanding of the concept of independent learning results in teachers finding it difficult to apply independent learning as they should. This writing answers the question of how teachers define independent learning and why teachers find it difficult to apply independent learning. The independent learning program aims to provide freedom of thought for teachers and students without being burdened by grades. The research location is SMA Negeri 2 Amahai Central Maluku. This type of research is qualitative where the teacher is the focus of the research and uses primary and secondary data. Data analysis was carried out in three stages, namely data reduction, data display and data verification. The results of the study show that there are three important elements that trigger teacher difficulties in defining and applying the concept of independent learning, namely 1) the teacher's long experience with conventional teaching and learning processes and being confronted with the concept of independent learning that has never been 2) the teacher's understanding is still limited about the meaning, the basis and principles of independent learning, and 3) the teacher lacks mastery of environmental and instrumental factors, for example, the curriculum and learning model of independent learning. Freedom of learning in reality is still understood in a limited way at the implementation level. Likewise with the immature teacher's readiness to apply learning with the concept of independent learning. It turns out that not all teachers know the concept of independent learning. The interpretation that professional teachers easily understand and apply independent learning in reality is not true. Independent learning is not mere science but procedural knowledge so that it is necessary to master factual understanding and experience about independent learning. Taking into account the limitations of time and research methods, it is necessary to carry out further research by paying attention to the quantitative elements of and the absorption of meaning and implementation of independent learning from teachers and students.